Harbinger of storm: influence of Oliver Sacks on levodopa therapy in early 1970s - Santos-Lobato, Bruno Lopes dos; Tumas, Vitor (Arquivos de Neuro-Psiquiatria, 2016)
Most known by his literary ability, the words of the neurologist Oliver Sacks (1933-2015) also had an impact on scientific community about the role of levodopa on parkinsonisms. Different from the most authors and based on his experience described on the book “Awakenings”, he had a pessimistic opinion about levodopa, which was related on many articles written by himself and colleagues in early 1970s. We reviewed the scientific contribution of Oliver Sacks associated to levodopa therapy on parkinsonisms, and how he advised caution with its complications before the majority of physicians.
Keywords: Oliver Sacks; Parkinson’s disease; levodopa; dyskinesias